Caracterización de las empresas pymes importadoras de Palmira: búsqueda de un mercado sustituto a nivel regional, conforme a los inconvenientes en las fluctuaciones de la tasa de cambio. (2020)
In recent years, the volatility of the currency (USD) in Colombia has had an impact on various sectors of society, especially for those spheres that obtain raw materials and imports, in this sense the work proposed as an objective to characterize companies’ importers in Palmira-Valle del Cauca, contributing to the search for a substitute market at the regional level, which allows the supply of Vallecaucana companies that at the international level can supply the Palmira sector. For this purpose, the method that was carried out was an exploratory, descriptive study with small and medium-sized companies in the municipality of Palmira, through a survey by analysis of variables, carried out on 36 companies in the City, (31 small and 5 medium). Among the conclusions, it was found that 89% of the small companies and 100% of the medium-sized companies surveyed acknowledge that they have been affected by currency fluctuations, and it was also found that in the Valle del Cauca region there are companies with possibility of serving as substitute markets for SMEs in Palmira, which can ensure a favorable closed economy, which would somehow strengthen economic growth in the region.